2023
DOI: 10.1371/journal.pone.0281750
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2 polymorphism (rs12329760) and the severity of the COVID-19 in Iranian population

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has been responsible for the recent pandemic since early 2020. Due to the wide range of clinical symptoms of this disease, from asymptomatic to severe and critical forms, it seems that genetic differences among patients, along with other factors (such as gender, age, and underlying diseases), can explain part of the variation in disease symptoms. The TMPRSS2 enzyme plays a vital role in the early stages of the interaction of the SARS-CoV-2 with the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
0
12
0
2
Order By: Relevance
“…The rs12329769 in TMPRSS2 in a recessive genetic model (CC + CT vs. TT) has been associated with severe COVID-19 and high levels of inflammatory markers such as C-reactive protein (CRP), ferritin, LDH, and D-Dimer [ 23 ]. The role of TMPRSS2 in cell entry of SARS-CoV-2 could explain the association with COVID-19 susceptibility found in some studies [ 38 ]. The missense variant rs12329769 (Val197Met) is in the coding part of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…The rs12329769 in TMPRSS2 in a recessive genetic model (CC + CT vs. TT) has been associated with severe COVID-19 and high levels of inflammatory markers such as C-reactive protein (CRP), ferritin, LDH, and D-Dimer [ 23 ]. The role of TMPRSS2 in cell entry of SARS-CoV-2 could explain the association with COVID-19 susceptibility found in some studies [ 38 ]. The missense variant rs12329769 (Val197Met) is in the coding part of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 21 single nucleotide variants (SNVs) in the TMPRSS2 gene, a computational study has revealed that the p.Val197Met variant affects this enzyme's structure by creating a pocket in the protein structure. This can lower enzyme activity and stability, which is anticipated to protect against SARS-CoV-2 infection by reducing SARS-CoV-2 activation and entrance into host cells [ 6 – 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, none of those differences were statistically significant, with a p -value of 0.074. Additionally, the study discovered a statistically significant link between COVID-19 severity and the minor T allele [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The rs12329760 has been suggested as one of the candidate polymorphisms to justify the high incidence and SARS-CoV-2 infection-related mortality rate in Italians, when compared to other European populations. 40 Yaghoobi et al 41 reported that in Iranian patients, the T allele of rs12329760 can be considered a risk allele for severe COVID-19. In contrast, previous studies on this variant in European populations have suggested that the T allele has a protective effect.…”
Section: Genetic Variants Associated With Covid-19mentioning
confidence: 99%